Evaluating and comparing the effect of two liquid polishes on the polish retention of two nanocomposites - Fatemeh Kazemi Bidhendi; Mahshid Mohammadi Basir; Mohammad Bagher Rezvani; Ali Khodabakhsh; Hossein Labbaf; Mohammad Amin Fahimi (Tehran University of Medical Sciences, 2022)
Background and Aims: Finishing and polishing of composites is a critical step influencing the clinical service of restorations. The aim of this article was to evaluate and compare the effect of two liquid polishes on the polish retention of two nanocomposites. Materials and Methods: Eighty standardized disk-shaped specimens (4×2 mm) were prepared from two nanocomposites (n=40), including one nano-filled composite (Filtek Z350 XT-3M ESPE, USA) and one nano-hybrid composite (Aelite Aesthetic Enamel-Bisco, Inc. Schaumburg, USA). The specimens were randomly divided into 4 subgroups (n=10) based on the method of finishing (F) and polishing (P) procedures: M: as control, polymerized under Mylar strip; S: finish and polish with a sequence of Sof-Lex discs (3M ESPE, USA); SP: finish and polish with Sof-Lex discs and use of Permaseal liquid polish (Ultradent products, Inc. USA); SB: finish and polish with Sof-Lex discs and use of Biscover liquid polish (Bisco, Inc. Schaumburg, USA). The specimens were undergone pH cycling and brushing machine and then, the average surface roughness (Ra) and average profile changes along the desired area (Rz) of the specimens were determined with profilometer instrument. Two-way and one-way analysis of variance (ANOVA) was used to compare the mean of surface roughness. Then, Tukey test was used to identify the groups responsible for the difference and t-test was used to compare the mean of surface roughness. Results: The type of composite and the method of polishing procedure had no effect on the mean Ra (P=0.733) but it had significant effect on Rz1 factor (P=0.025). Conclusion: Using liquid polish after polishing discs had no effect on the polish retention of nanocomposites.